2013
DOI: 10.6061/clinics/2013(04)03
|View full text |Cite
|
Sign up to set email alerts
|

Cognition and biomarkers of oxidative stress in obstructive sleep apnea

Abstract: OBJECTIVES:The aim of this study was to investigate neuropsychological performance and biomarkers of oxidative stress in patients with obstructive sleep apnea and the relationships between these factors.METHODS:This was an observational, cross-sectional study of 14 patients (36.0±6.5 years old) with obstructive sleep apnea and 13 controls (37.3±6.9 years old). All of the participants were clinically evaluated and underwent full-night polysomnography as well as neuropsychological tests. Blood samples were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 66 publications
2
27
0
1
Order By: Relevance
“…Both OSAHS and Hcy are considered as independent risk factors for cardiovascular disease. [11] Thakre et al [12] have found that the level of Hcy in OSAHS people was significantly higher than that in non-OSAHS people, Sales et al [13] also came to similar results in their research. Animal models have confirmed that the level of Hcy in OSAHS rats is higher than that in non-OSAHS rats; hypoxic changes in OSAHS rats may result from the fact that increased level of Hcy enhances inflammatory responses in the body and leads to the occurrence of AS in cerebral arteries.…”
Section: Discussionsupporting
confidence: 71%
“…Both OSAHS and Hcy are considered as independent risk factors for cardiovascular disease. [11] Thakre et al [12] have found that the level of Hcy in OSAHS people was significantly higher than that in non-OSAHS people, Sales et al [13] also came to similar results in their research. Animal models have confirmed that the level of Hcy in OSAHS rats is higher than that in non-OSAHS rats; hypoxic changes in OSAHS rats may result from the fact that increased level of Hcy enhances inflammatory responses in the body and leads to the occurrence of AS in cerebral arteries.…”
Section: Discussionsupporting
confidence: 71%
“…We excluded 220 duplicated articles and additional 445 articles that did not satisfy the selection criteria. After reviewing the full texts of the remaining 30 articles, 20 articles were excluded because of the following reasons: not relevant to our analysis ( n = 5) [14,17,[21][22][23], insufficient data ( n = 11) [12,15,16,[24][25][26][27][28][29][30][31] , shared an identical study population with other articles ( n = 1) [19], data from preexisting dementia [32] , using dementia mortality as a result [33] , and using an acute biomarker as exposure [34] . The remaining 10 studies (3 case-control studies [10,11,35] and 7 cohort studies [36][37][38][39][40][41][42] were included in the final analysis.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Singh et al [95], supplementing OSA patients with vitamins E and C concluded that that antioxidant treatment (oral vitamin E and C) reduced oxidative stress in OSA patients. Furthermore, decreased levels of antioxidants (superoxide dismutase, catalase, glutathione and homocysteine, as well as vitamins E, C, B11 and B12) and lower performance on the neuropsychological tasks were observed in patients with obstructive sleep apnea [96]. The authors suggest that an imbalance between antioxidants and pro-oxidants may contribute to neuropsychological alterations in this patient population.…”
Section: Vitamin Cmentioning
confidence: 88%